Sentidos do zero - Guimarães, Fabiane (2008)
In this work, the students of Education Child Schooling including studentes Education of young people and adults were interviewed on what they think about the zero, which senses atribute him. Students from different series in ages (ETHNO), to explain (MATHEMA) zero, used different technical (TICS). Using precepts of qualitative research and based on the theory of knowledge Ethnomathematics the TICS of MATHEMA were grouped into units of meaning. The zero was perceived as: a technique mathematical, a concept, a technique in the service of social and as metaphor, The work is organized into three chapters: The chapter zero brings the thinking initials, theoretical and methodological; The chapter I brings reflections on the historical zero. And finally in chapter II are the stories of students on zero